2001
DOI: 10.1053/jars.2001.20661
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic double-bundle posterior cruciate ligament reconstruction using hamstring tendons

Abstract: Recent biomechanical studies have shown that an anatomic double-bundle posterior cruciate ligament (PCL) reconstruction is superior in restoring normal knee laxity compared with the conventional single-bundle isometric reconstruction. We describe a modification of an endoscopic PCL reconstruction technique using a double-bundle Y-shaped hamstring tendon graft. A double-or triple-bundle semitendinosus-gracilis tendon graft is used and directly fixed with soft threaded biodegradable interference screws. In the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 48 publications
0
19
2
6
Order By: Relevance
“…Other studies have reported the transverse lengths at the femoral insertion, central portion and tibial insertion levels (Triantafyllidi et al;Fanelli et al;Sheps et al, 2005;Margheritini et al, 2004;Cosgarea & Jay, 2001;Stähelin et al, 2001). Harner et al (1999) discovered that the AL fascicle is greater than the PM, which differs from data reported by Takahashi The most relevant finding of this study was that the PCL did not have the same dimension for the entirety of its length, replicating the "sand clock" form with wide bases and a thin center, particularly in its anteroposterior length.…”
Section: Discussioncontrasting
confidence: 82%
“…Other studies have reported the transverse lengths at the femoral insertion, central portion and tibial insertion levels (Triantafyllidi et al;Fanelli et al;Sheps et al, 2005;Margheritini et al, 2004;Cosgarea & Jay, 2001;Stähelin et al, 2001). Harner et al (1999) discovered that the AL fascicle is greater than the PM, which differs from data reported by Takahashi The most relevant finding of this study was that the PCL did not have the same dimension for the entirety of its length, replicating the "sand clock" form with wide bases and a thin center, particularly in its anteroposterior length.…”
Section: Discussioncontrasting
confidence: 82%
“…These PCL reconstruction techniques (single graft and double graft reconstructions) have been compared in previous experimental studies (Bergfeld et al, 2001;Hagemeister et al, 2002;Mannor et al, 2000;Race and Amis, 1996;Race and Amis, 1998;Stahelin et al, 2001). Harner et al (2000b) have shown that the kinematics behavior of a knee with a ''native'' PCL and a knee with double graft reconstructed PCL were similar.…”
Section: Introductionmentioning
confidence: 99%
“…Restrictions relating to the limits on knee flexion gains are discussed in the literature, with divergences between the rehabilitation protocols presented. Some authors have prioritized limiting the range of angles to between 0 and 60º (7)(8)(9)(10) , 0 and 70º (11) , 0 and 90º (12)(13)(14)(15) or 0 and 120º (16) , or without any stimulated limit (17) or according to the patient's tolerance (18) . Quelard et al (19) recommended a gradual protocol for gaining passive mobility of the knee, such that a range of 0-60° would be achieved in the first six weeks, 0-90° from the sixth to the eighth week and 0-120° from the eighth week onwards.…”
Section: Points Relating To Rommentioning
confidence: 99%
“…However, other studies are divergent. Some authors have recommended that weight-bearing should be introduced according to the patient's tolerance and should be started in the first week (7,8,15,17,20,27,28) , while one study restricted weight-bearing until the sixth week (16) and others until the eighth week (11,18) . In some protocols, weight-bearing is not recommended during the first days after reconstruction.…”
Section: Release For Weight-bearing (Walking)mentioning
confidence: 99%